ANALISIS KEBIJAKAN UTANG PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI - Ruth Dessy Debora, - (2019)
This study aims to determine the effect of Asset Structure, Profitability, and Firm Size on Debt Policy. The population in this study are all property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 20152017 period. The sampling technique used was purposive sampling and obtained a sample of 29 companies. The data analysis technique used is descriptive analysis using Microsoft Excel 2016 and the hypothesis in this study uses Panel Data Regression Analysis with the E-views version 9.0 program. and a 5% significance level. Based on the test results show that (1) asset structure has not effect on debt policy, (2) profitability has positive effect on debt policy, (3) firm size has positive effect on debt policy.